Implications of changing shipping patterns near communities across Arctic Canada - Alison Cook; Jackie Dawson; Jean Holloway; Michael Milton; Shirley Tagalik; Kukik Baker; Jimmy Muckpah; Shelly Elverum; Elizabeth Boyse; Melody S. Clark; Clara Manno; Vicky Peck; et al. (Regional Environmental Change, 2026)
The increase in shipping in the Canadian Arctic has significant impacts on Inuit coastal communities and their traditional way of life. Examples include the risk of chemical spills, underwater noise and ships’ hulls acting as vectors for non-indigenous species, all of which impact ecosystems and wildlife which Inuit rely on for health, food security and cultural sustainability. However, the number and types of ships travelling near communities and the associated risks remain poorly quantified, limiting effective management strategies. We use ship tracklines generated from Automatic Identification System (AIS) ship positions between 2013 and 2022 to calculate voyages within 20 km of 43 communities distributed throughout Northern Canada (north of 60° N and Hudson Bay). Over 10 years, voyages increased significantly by a factor of 1.7 (from 116 in 2013 to 317 in 2022), with the largest increases due to dry bulk, cargo and government/research vessels. This varies between communities, with 15 (35%) having shown little change or a small decrease in shipping, and 28 (65%) showing an increase. Six communities accounted for the majority of the overall increase. We examine these sites in detail, identifying drivers behind the voyage increases such as the proximity to mines, growing resupply needs, tourism expansion and increased navigability along transit routes close by due to the reduction in sea ice. Our results on the rate and drivers of change in ship traffic provide essential insights for local and regional governance of shipping impacts.